Penerapan Pembinaan Intensif dalam Upaya Peningkatan Kinerja Tim Akreditasi di MTSn 2 Bener Meriah - Farida, Lasma (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
Intensive implementation of coaching to improve the performance of accreditation teams is the full responsibility of the leader of an institution or institution. Similarly, MTsN 2 Bener Meriah is one of the Islamic educational institutions. This study aims to find out how  the intensive application of coaching in an effort to improve the performance of the accreditation team MTsN 2 Bener Meriah. This research is qualitative with descriptive survey techniques. Through interviews, observations, and documentation, the following research results are found: (a) the components of accreditation that become the assessment points in the form of curriculum of each educational program, number of educators, the condition of learners, coordination of the implementation of education, educational facilities and infrastructure, readiness of academic administration, staffing, and household finances, (2) the application of coaching one of them on the components of content standards and process standards, (3) based on the evaluation of activities in the know that not fully the management of MTsN 2 Bener Meriah committed in carrying out the task and not yet maksimanya conflict management so that there is doubt and lack of readiness in maintaining the 'A grade' that has been achieved.